Pengembangan Karier dan Kinerja Karyawan: Peran Mediasi Kepuasan Kerja dan Motivasi Kerja pada Unit Mekaar PNM Cabang Palu - Zulkarnain Nurdin; Muh. Ashary Anshar; Andi Faisal Syam (Center of Economic Students Journal, 2026)
This study examines the effect of career development on employee performance through job satisfaction and work motivation at the Mekaar Unit of PNM Palu Branch. The study employed an explanatory quantitative approach with a cross-sectional design. Questionnaire data were collected from 100 respondents selected through purposive and quota sampling, comprising 60 operational employees and 40 employees at unit-head level or above. The model was analyzed using partial least squares structural equation modeling in SmartPLS 4. Career development had positive effects on job satisfaction (β = 0.664; p < 0.001), work motivation (β = 0.631; p < 0.001), and employee performance (β = 0.262; p = 0.001). Job satisfaction (β = 0.396; p < 0.001) and work motivation (β = 0.352; p < 0.001) also improved employee performance. Both indirect effects were significant through job satisfaction (β = 0.263; p < 0.001) and work motivation (β = 0.222; p < 0.001). The model explained 72.1% of the variance in employee performance and produced an SRMR value of 0.056. Because the direct effect remained significant, the two mediating mechanisms indicate complementary partial mediation. The findings show that career development improves performance not only by strengthening employee capabilities but also by creating satisfaction, expectations of advancement, and achievement-oriented motivation. PNM should therefore establish transparent career paths, fair promotion assessments, relevant development programs, and consistent recognition and supervisory support.